Implementation of the Project Based Learning Method in English Speaking Skills for Diploma III Culinary Management Students - Kadek Feni Aryati; Putu Sri Darmayanti; I Putu David Adi Saputra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The use of inappropriate learning methods can make the teaching and learning process ineffective and cause learning objectives to not be achieved. A lack of creativity from lecturers in adapting learning methods to the needs and conditions of students, especially in the Culinary Management department, is a major cause. DIII Culinary Management students, who will later become professional chefs in hotels and restaurants, need good English speaking skills to communicate with foreign guests, understand international recipes, and adapt to a global work environment. This research aims to: 1) implement the Project Based Learning (PBL) method in English speaking skills learning for DIII Culinary Management students; 2) analyze the effectiveness of PBL in improving students' English speaking skills; and 3) develop a PBL-based English learning module integrated with the Culinary Management curriculum. This research will use a mixed methods research approach to examine the effectiveness of implementing Project Based Learning (PBL) in improving the English speaking skills of DIII Culinary Management students. This research will make a significant contribution to the development of English language learning in the Culinary Management study program, particularly in improving students' speaking skills. The research results can be used to improve learning methods and curriculum, so that students can be better prepared to face the world of work.